Development Of Novel Therapeutics Targeting Transient Receptor Potential Channel Mediated Nociception For The Treatment Of Chemotherapy-induced Neuropathic Pain - Akhilesh (IIT(BHU) Varanasi, 2024)
Abstract is available in the attachment.
Keywords: Pharmaceutical Engineering